Musculoskeletal pain as a predictor for depression in the general working population of Denmark. Issue 6 (August 2021) - Hannerz, Harald; Holtermann, Andreas; Madsen, Ida Elisabeth Huitfeldt
Aim: This study examines the association between musculoskeletal complaints and subsequent use of antidepressants and/or psychiatric hospital treatment for depressive mood disorders in the Danish labour force. Methods: The study is based on two cohorts. The first cohort is the total labour force in 21 Danish municipalities ( n =693, 860), where the risk of depression (psychiatric diagnosis or antidepressant treatment) during 2010–2015 was compared between individuals on long-term sickness absence due to musculoskeletal disorders (MSD) and non-sick-listed gainfully employed individuals. The second cohort is a random sample of the Danish labour force ( n =9248) who were followed during 2011–2015 to estimate the association between self-rated musculoskeletal pain and depression. All analyses were controlled for age, sex, calendar period and socio-economic status. Results: Compared to non-sick-listed gainfully employed individuals, there was an increased risk of depression in individuals sick-listed with MSD, with rate ratios of 2.39 (99% confidence interval (CI) 2.22–2.58) for individuals with less severe MSD and 4.27 (99% CI 3.98–4.59) for individuals with more severe MSD. There was also an increased risk of depression associated with self-rated pain (yes vs. no), with a rate ratio of 2.17 (99% CI 1.69–2.78). The population attributable fraction of depression from musculoskeletal pain was 0.35 (99% CI 0.24–0.45). Conclusions: The results of the present study indicate that musculoskeletal pain is an important predictor of indicators of depression in the general working population of Denmark.